2020
DOI: 10.1021/jacs.0c01349
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Rock Salt Oxide-Mediated Synthesis of High-Density Dual-Protected M@NC for Long-Life Rechargeable Zinc–Air Batteries with Record Power Density

Abstract: Creating high-density durable bifunctional active sites in an air electrode is essential but still challenging for a long-life rechargeable zinc–air battery with appealing power density. Herein, we discover a general strategy mediated by metastable rock salt oxides for achieving high-density well-defined transition-metal nanocrystals encapsulated in N-doped carbon shells (M@NC) which are anchored on a substrate by a porous carbon network as highly active and durable bifunctional catalytic sites. Small-size (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(126 citation statements)
references
References 52 publications
1
122
0
Order By: Relevance
“…The transfer number of ≈4 indicates the predominant 4‐electron transfer process for OH − yielding. [ 51–53 ] MnS also shows a fair OER activity with a potential of 1.813 V at 10 mA cm −2 ( E j =10 ). While the ORR activity of Ni x Co 1− x S 2 ( E 1/2 = 0.710 V) is inferior to MnS, Ni x Co 1− x S 2 material shows a more favorable OER activity indicated by a E j =10 of 1.610 V. It suggests that the introduction of Ni x Co 1− x S 2 into the MnS will realize a significant improvement of the OER activity.…”
Section: Resultsmentioning
confidence: 99%
“…The transfer number of ≈4 indicates the predominant 4‐electron transfer process for OH − yielding. [ 51–53 ] MnS also shows a fair OER activity with a potential of 1.813 V at 10 mA cm −2 ( E j =10 ). While the ORR activity of Ni x Co 1− x S 2 ( E 1/2 = 0.710 V) is inferior to MnS, Ni x Co 1− x S 2 material shows a more favorable OER activity indicated by a E j =10 of 1.610 V. It suggests that the introduction of Ni x Co 1− x S 2 into the MnS will realize a significant improvement of the OER activity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been reported that SCN − is poisonous for Fe−N x sites in the catalysis of ORR, [53] so the RDE measurements of the oxygen reduction activity of PBCs‐900 in 0.1 M KOH with and without the addition of 10 mM KSCN were performed. It can be seen from Figure 6f that no obvious change occurs for the onset potential of PBCs‐900 with and without SCN − , but the E 1/2 and J L of PBCs‐900 with the addition of SCN − decreases by ∼40 mV and ∼0.4 mA cm −2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…After the acid leaching process, the N 1s high resolution spectrum and the contents of the total N species of acid-leached PBCs-900 were shown in Figure 6d and Figure 6e, respectively. It can be seen from the deconvoluted N 1s high-resolution spectra that the content of total N species and the percentage of pyridinic N in total N species for acidleached PBCs-900 decreased remarkably compared with that of PBCs-900, this may due to the wreck of FeÀ N bond and protonation pyridinic-N. [52] On the other hand, it has been reported that SCN À is poisonous for FeÀ N x sites in the catalysis of ORR, [53] so the RDE measurements of the oxygen reduction activity of PBCs-900 in 0.1 M KOH with and without the addition of 10 mM KSCN were performed. It can be seen from Figure 6f that no obvious change occurs for the onset potential of PBCs-900 with and without SCN À , but the E 1/2 and J L of PBCs-900 with the addition of SCN À decreases by ∼ 40 mV and ∼ 0.4 mA cm À 2 , respectively.…”
Section: Electrochemical Characterizationsmentioning
confidence: 99%
“…Very recently, we discovered a metastable rocksalt oxidemediated strategy. It was able to produce small-size, highdensity, uniformly-distributed, and well-protected M@NC sites [94]. To avoid the uncontrollable thermal decomposition and inevitable aggregation of metal nanoparticles, prepreparing well-dispersed precursors such as metal oxide nanoparticles on support instead of direct pyrolysis of metal sources would be an option for achieving the goal.…”
Section: Metastable Rocksalt-oxide Mediated Strategymentioning
confidence: 99%
“…a) Scheme for the synthesis of high-density well-dispersed Co 2 Fe 1 @NC via a rocksalt oxide-mediated strategy; (b) overview SEM image, (c) HRSEM image, and (d) HRTEM image of Co 2 Fe 1 @NC; (e) Zn-air performance and (f, g) long-time cycling of the devices with Co 2 Fe 1 @NC and Pt/C-IrO 2 . Adapted with permission from Ref [94],. Copyright by the American Chemical Society (color online).…”
mentioning
confidence: 99%